Ritual of Veni Bharan - Mumbai Archive Project Team (Jio Institute, 2024)
A special ritual known as veni bharan involves placing a floral veni on Holika’s hair to complete her bridal appearance. A veni is a hair accessory made by stringing together fresh flowers such as jasmine, roses, and marigolds into a circular or crescent-shaped garland.